2013
DOI: 10.1128/jcm.02056-13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of a Real-Time PCR Assay for Identification of Salmonella, Shigella, Campylobacter (Campylobacter jejuni and C. coli), and Shiga Toxin-Producing Escherichia coli Isolates in Stool Specimens

Abstract: e Enteric illness affects millions of individuals annually in the United States and results in >50,000 hospitalizations. The rapid and accurate identification of bacterial pathogens associated with gastroenteritis can aid acute patient management decisions, including the use of antibiotic therapy and infection control. This study compared the ProGastro SSCS multiplex real-time PCR assay (Gen-Probe Prodesse, San Diego, CA) to culture for the identification of Campylobacter spp. (Campylobacter jejuni and Campylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 26 publications
3
47
2
Order By: Relevance
“…A review of the literature indicates that the performance of the BD Max EBP assay is similar to those of other multiplex assays developed recently. The sensitivity and specificity of the Prodesse ProGastro SSCS assay compared to culture and EIA determined by one multicenter study of 1,244 specimens were 100% and Ն99.4%, respectively, for all four bacterial targets (9). Early studies of the Luminex xTAG GPP assay demonstrated sensitivities ranging from 83 to 93% for Salmonella spp., 90 to 97% for Campylobacter spp., 93 to 100% for Shigella spp., and 94% to 100% for STEC (6,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the literature indicates that the performance of the BD Max EBP assay is similar to those of other multiplex assays developed recently. The sensitivity and specificity of the Prodesse ProGastro SSCS assay compared to culture and EIA determined by one multicenter study of 1,244 specimens were 100% and Ն99.4%, respectively, for all four bacterial targets (9). Early studies of the Luminex xTAG GPP assay demonstrated sensitivities ranging from 83 to 93% for Salmonella spp., 90 to 97% for Campylobacter spp., 93 to 100% for Shigella spp., and 94% to 100% for STEC (6,21).…”
Section: Discussionmentioning
confidence: 99%
“…These systems use a variety of approaches and differ as to the number and type of targets incorporated in the assay and the overall platform design and throughput. The Prodesse ProGastro SSCS assay (Gen-Probe Prodesse, San Diego, CA) detects the same pathogens as those detected by the BD Max EBP assay, but unlike the BD Max assay, the ProGastro SSCS assay requires external extraction on a separate instrument, increasing the hands-on time and technical complexity (9). Other systems have been designed to detect viral and parasitic enteric pathogens as well as additional bacterial targets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also provides real-world data in which informed considerations can be made on whether and how Campylobacter case definitions should be modified in the future. Highly sensitive and more specific nucleic acid amplification assays have more recently been approved by the FDA and may be preferable to stool antigen assays as alternatives to culture for detecting Campylobacter in stool (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Given the low prevalence of STEC infections (1 to 2%) (11)(12)(13), the associated costs for clinical laboratories for personnel, equipment, and reagents are major barriers for implementation of the recommended universal screening of stool for STEC (4,14). To reduce testing costs, we evaluated the feasibility of a pooled nucleic acid amplification test (NAAT) as an approach for low-cost high-throughput screening for stx 1 and stx 2 from stool.…”
mentioning
confidence: 99%